Analisis Tentang Tobacco Plainpackaging Act In Australia dan Implikasinya Terhadap Perdagangan Internasional Indonesia - Syahmin AK; Fidelia Syahmin (Universitas Sriwijaya, 2017)
World Trade Organization (WTO) as the international organization under the United Nations has its own trade provisions obligated to its contracting parties. During the exsitance of WTO, there are many cases found from the provision of some contracting parties that are not in accordance with General Agree-ment on Tariff and Trade (GATT) and the other following agreements. One of the case found is Australia„s decision on The National Treatment Enforcement for every domestic and imported tobacco products (cigarettes) which sold in Australia trade area which known as Tobacco Plain Packaging Act. As for the purpose of that act is to increase the society awareness of healthy living by avoiding the tobacco consump-tion impacts. Based on those purpose, this research had been focused on the juridicial review of the har-mony between Australia„s internal regulation towards GATT and the other WTO multilateral agree-ment. As for the result those research, it is found that The National Treatment enforcement of these tobacco products standardization are unsuitable towards GATT and the Techincal Barriers to Trade (TBT) Agreement. In addition, it can be concluded that Australia„s internal regulation are not in accor-dance with the consensus of the other contracting parties under the WTO Multilateral agreements.Keywords: Tobacco PlainPackagingAct, Australia, International Trade, Indonesia.